In the Aftermath of Gezi
XII, 219 p. 1 illus.
Keywords: This edited volume addresses various aspects of social and political development in Turkey and the latter’s role within a global context. Paradigmatically and theoretically, it is situated in the realm of communication and/for social change. The chapters thread together to present a fresh and innovative study that explores an array of issues related to the Gezi protests and their aftermath by scholars and activists from Scandinavia, Turkey and India. Through its thorough analysis of the government’s repressive policy and the communication strategies of resistance, during the protests as well as in the dramatic on-going aftermath, the volume has wide international and interdisciplinary appeal, suitable for those with an interest in globalization, communication and media, politics, and social change. .